2001
DOI: 10.2166/wqrj.2001.028
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Low pH on the Microfauna of an Activated Sludge Wastewater Treatment System

Abstract: Optimum pH for biological (e.g., activated sludge) wastewater treatment is stated to lie between pH 6.5 and 8.0; however, the pH of processed effluent from thermomechanical pulp mills is closer to 4.5 and 5.5. Consequently, pH adjustment of effluent is required with associated costs. The ability of the microfaunal community (protozoa and metazoa) of activated sludge to survive at pH levels below 6.5 was evaluated with samples collected from Corner Brook Pulp and Paper Ltd. (Newfoundland, Canada). Effect of pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…The mixed liquor pH increased from 7.1 to 8.3 and 7.2 to 8.4 for the anoxic and the aerobic bioreactors, respectively following ammonia shock. In agreement with Trinh (2013), the pH levels returned to the normal operation range within 72 h. Such temporary pH variation may not significantly affect bulk organics removal since the optimum pH for biological process is thought to lie between pH 6.5 and 8.0 (Baldwin and Campbell, 2001). However, this may have significant impact on the removal of some specific TrOCs as further discussed in Section 3.3.…”
Section: Ph and Orpsupporting
confidence: 84%
“…The mixed liquor pH increased from 7.1 to 8.3 and 7.2 to 8.4 for the anoxic and the aerobic bioreactors, respectively following ammonia shock. In agreement with Trinh (2013), the pH levels returned to the normal operation range within 72 h. Such temporary pH variation may not significantly affect bulk organics removal since the optimum pH for biological process is thought to lie between pH 6.5 and 8.0 (Baldwin and Campbell, 2001). However, this may have significant impact on the removal of some specific TrOCs as further discussed in Section 3.3.…”
Section: Ph and Orpsupporting
confidence: 84%
“…The pH during all experiments varied in the range of 6.9 to 7.9 while increasing continuously during each experiment. This range of pH is conformant to the optimum conditions for biological wastewater treatment, according to Baldwin and Campbell (2001). The observed increase in pH indicated no accumulation of acidic intermediates formed during the biodegradation (Chavan & Mukherji, 2010).…”
Section: Overview Of Process Performancesupporting
confidence: 61%
“…Meanwhile, as the mixed liquor pH decreased to 5.5 and below, the microbial activity has worsen revealing low %COD removal. Thus, low pH can interfere with the degradation mechanism of some bacterial species [21] [22] including Bacillus and Pseudomonas. Additionally, Bhattacharyya et al [23] reported that heterotrophic bacteria favor the operation in pH in the range of 7.2 -8.5 [24] [25].…”
Section: Effect Of Phmentioning
confidence: 99%